Evaluation of CT dose and establishment of local DRLs for abdomen and pelvis examinations in hospitals in Taif City, Saudi Arabia - Osman, Hamid; Alosaimi, Maathir; Alghamdi, Fai; Aljuaid, Atheer; Alqurashi, Manar; Aldajani, Shihanah; Faizo, Nahla L.; Alamri, Sultan; Althobaiti, Yazeed S.; Khandaker, Mayeen Uddin *; Suleiman, Abdelmoneim (Elsevier, 2023)
This study measures the CT dose of the abdomen and pelvic examinations for adult patients, as well as establishes the provincial diagnostic reference level (DRL) for hospitals in Taif city, Saudi Arabia. A total of 200 patients who underwent pelvis and abdomen examinations in two main hospitals in Taif city were selected for this study. The data were collected in a spreadsheet that records patients’ demographic data, exposure parameters and dose indicators such as dose length product (DLP) and volume computed tomography dose index (CTDIvol) for each examination. The patients’ average age and BMI were 37.3 years and 25.5 kg/m2, respectively. The mean DLP and CTDIvol for the pelvis were found to be 379.6 mGy-cm and 10.8 mGy, respectively, whereas the corresponding mean values for the abdomen were 369.5 mGy-cm and 11.5 mGy, respectively. The average effective dosages for the abdomen and pelvis in both hospitals were estimated to be 5.6 and 7.2 mSv, respectively. Based on the third quartile data of DLP and CTDIvol, this study suggests DRL for pelvic DLP and CTDIw are 402.5 mGycm and 21.8 mGy, respectively, whereas the respective values are 407.5 mGy-cm and 18.4 mGy for CT abdominal DLP and CTDIw. The present study reports lower values for effective dose and DRL when compared with earlier data available in the literature. However, this work suggests further studies with different kV stations on pediatric patients in the future.